Le droit d’asile contemporain : la protection rattrapée par le contrôle des frontières ? - Camille de Vulpillières (Diasporas: Circulations, Migrations, Histoire)
This article aims to examine the tensions that exist within the contemporary asylum system. The first part analyses the general framework of contemporary asylum law to show that it contains two competing conceptions: one that views asylum as an individual right to protection, and the other that views it as a discretionary grant of protection. The second part examines recent developments in the asylum system to show that they accentuate the imbalance in favour of the discretionary granting of asylum, to the extent of jeopardizing the effective protection of refugees.